Vitis vinifera—Forceful Rebellion while Feeling Bounded by Responsibilities - Flores, Matilde (Homœopathic Links, 2017)
A case of recurrent diverticulitis responds to Vitis vinifera and a few years after the prescription, Vitis vinifera's place in the plant kingdom is nicely confirmed by Jan Scholten's Plant Theory.
Keywords: Plant theory; Vitaceae; Vitis vinifera; Grape vine